Nitrogen-Doped Oxygenated Molybdenum Phosphide as an Efficient Electrocatalyst for Hydrogen Evolution in Alkaline Media - Khan, Muhammad Waqas; Loomba, Suraj; Ali, Rashad; Mohiuddin, Md; Alluqmani, Ahmed; Haque, Farjana; Liu, Yongkun; Sagar, Rizwan Ur Rehman; Zavabeti, Ali; Alkathiri, Turki; Shabbir, Babar; Jian, Xian; et al. (Frontiers in Chemistry, 2020)
Phosphides of transition metals (TMPs) are a developing class of materials for hydrogen evolution reaction (HER) as an alternative to expensive noble metals to produce clean energy. Herein, the nitrogen-doped molybdenum oxide (MoOx) is developed via a facile and simple hydrothermal method, followed by annealing in the N2 atmosphere and phosphorization to form a nitrogen-doped oxygenated molybdenum phosphide (N-MoP) sphere-shaped structure. The developed N-doped phosphide structure depicts enhanced HER activity by reaching a current density of 10 mA cm−2 at a very low overpotential of only 87 mV, which is much better than annealed nitrogen-doped molybdenum oxide (A-MoOx) 138 mV in alkaline medium. N-MoP is a highly efficient electrocatalyst for HER attributed to a more exposed surface, large electrode/electrolyte interface and appropriate binding energies for reactants. This study extends the opportunity of developing nitrogen-doped TMPs, which can display exceptional properties as compared to their oxides.